Differential Effects of Cyclosporin A and Tacrolimus on Magnesium Influx in Caco2 Cells - Elodie Gouadon; Florence Lecerf; Michèle German-Fattal (Frontiers Media S.A., 2012)
PURPOSE: Hypomagnesemia with urinary magnesium (Mg) wasting is a well acknowledged side effect of cyclosporin A (CsA) and tacrolimus (FK506) treatments. TRPM6, TRPM7 and MagT1 are involved in the active transcellular Mg transport processes in intestine and kidney. Since Mg homeostasis is tightly controlled by the dynamic action of intestinal absorption of dietary Mg and renal excretion of Mg, we investigated whether CsA and FK506 in commercially available solutions for clinical use decrease the expression and the function of TRPM6, TRPM7 or MagT1 in the intestinal epithelial cell line Caco2. METHODS: Changes of intracellular free Mg concentrations were measured by Mag-fura-2 imaging in Mg-free medium after the addition of 1 mM MgCl2. TRPM6, TRPM7 and MagT1 were evidenced in cells by immunofluorescence. Proteins and mRNAs were quantified after 18 hours of treatment with CsA or FK506 by western-blot and real-time RT-PCR analyses, respectively. RESULTS: TRPM6 and MagT1 were evidenced on all cell membranes, TRPM7 only on the inner membranes. CsA was responsible for a profound decrease in Mg2+ influx in intestinal epithelial cells, which may result in a decrease of intestinal Mg absorption, whereas FK506 was responsible for a marked increase in Mg2+ influx. Neither CsA nor FK506 altered TRPM6, TRPM7 or MagT1 mRNA levels or MagT1 protein level. CONCLUSIONS: In Caco2 cells, Mg2+ influx was inhibited by CsA solutions whereas enhanced by FK506 solutions, without alteration of MagT1, TRPM6 and TRPM7 expression, leading to the conclusion that CsA and FK506 have opposite effects in the functional activity of the Mg transporters herein examined. In clinical use, FK506 should be preferred for patients at risk for hypomagnesemia. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.